Análise espaço temporal e epidemiológica da síndrome da imunodeficiência adquirida dos pacientes em terapia antirretroviral em município do Centro-Sul do Brasil - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
Introduction: The AIDS epidemic has proved to be a global phenomenon, continuous and unstable, the dynamicity of the epidemiological profile of the disease and the alarming rates of morbidity and mortality have made this a challenge and a serious public health problem. Objective: To describe the trend and spatial distribution of HIV / AIDS incidence coefficients in the population of the city of Ponta Grossa from 2002 to 2015. Methods: Epidemiological study with mixed ecological design and retrospective cohort among PLHA patients assisted by the Specialized Attention Service of thecity of Ponta Grossa. The data were collected based on the records of the medical records and the records of notification of diseases of patients in ART. The variables of interest for the study were: address, neighborhood, city of residence, date of diagnosis, sex, date of birth, race / color, education at time of notification, occupation, marital status, mode of transmission and sexual behavior. A descriptive analysis of the variables was performed, as well as the AIDS incidence rate per year and the mean age at the time of notification. The incidence rates of AIDS were organized for three years in order to verify the occurrence of association between the rates and the variables of interest in the study. Thematic maps were constructed to verify the incidence of HIV / AIDS coefficients by neighborhoods. In order to verify the concentration of cases in the districts of the city, the Kernel density estimation technique was used. Fuzzy logic was used to identify the distinct groups related to gender and age. Results: From 2002 to 2015, data were collected from 512 patients diagnosed with HIV / AIDS in ART. It was found that 58.5% were male. The mean age was 37.17 (SD = 11.34). 84.4% were white, 47.5% were married with heterosexual behavior (87.8%). 68.8% had completed high school and 22.8% were from the home. There was a 586% increase in AIDS rates in the study period, there was an increase in rates for the men during the study, from 33.50% to 26.83% among women in the study period. 2010 to 2015. The age group of 30 to 39 years presented the highest AIDS rate during the triennium, except for the triennium 2008- 2010. For the age group 50-79, the highest AIDS rate occurred in the biennium 2014- 2015, 45.09% (95% CI 30.64 - 64.00), with constant growth over time. The Piriquitos neighborhood had the highest incidence rate in all three years, in the biennium 2014- 2015 the highest incidence rate in the Colonia Dona Luiza neighborhood, followed by Centroneighborhood. Conclusion: The information gathered in this study shows the need for interdisciplinary actions combining education and guidance by multiprofessional groups. It is also concluded that technologies related to spatial analysis can be favorable to monitoring and preventive actions in the surveillance and control of the spread of the disease.
Keywords: Síndrome de Imunodeficiência Adquirida; Análise espacial; Perfil epidemiológico; Incidência; Acquired Immunodeficiency Syndrome; Spatial analysis; Epidemiological profile; Incidence; CNPQ::CIENCIAS DA SAUDE